The Effect of Surfactant, Time and Speed of Stirring in the Emulsification Process of Soybean Oil in Water - Hariyatno, Shelvin Putri; Paramita, Vita; Amalia, Rizka (Vocational College of Universitas Diponegoro, 2021)
Homogenization is the process of uniform particle size in an effort to maintain the stability of a mixture which is formed from 2 incompatible phases or so-called emulsion.Emulsion is a complex system consisting of a liquid phase which is spread over another immiscible liquid phase which is usually through mechanical shear. All emulsions are thermodynamically unstable due to contact between oil and water molecules. However, emulsions can be stabilized rapidly in the presence of emulsifying or thickening agents such as Tween 20 and Tween 80. Apart from the addition of emulsion stabilizing surfactants, the speed of stirring also has an effect in stabilizing the emulsion. This research was conducted to determine the effect of stirring speed and addition of surfactants Tween 20 and Tween 80 on the stability of soybean oil emulsion. The results of density, viscosity, stability, and microscopic tests showed that the emulsion was treated with the addition of tween 80 with a stirring speed of 30.